Sexual Appeals as marketing tool and its influence on consumers - Kumbhat, Priyanka (2017)
This research paper examines the way consumers are influenced when exposed to sexual appeal advertising and how they perceive and relate with such a phenomena. Though there are various studies that have been carried out to understand the motive and usage of sexual appeals as a marketing tool, there hasn’t been a lot of attention paid towards understanding the implications consumers associate sexual appeals with based on personal mentality and aspirations. The explorative study aims at examining the stimuli reaction and psychology of consumers as a result of a reaction towards sexual appeal used in marketing/advertising. By exploring these concepts, the research dwells upon the effect sexual stimulus have on the purchase behavior and intention of consumers residing in Dubai, Middle East. The research has adopted a qualitative approach to understand the human emotions and viewpoints behind individual associations consumers make when exposed to sexual appeals. In-depth interview were conducting by implementing the Zaltman Metaphor Elicitation Technique to understand the thoughts of consumers that they might be unaware of themselves. The ZMET technique has been utlised for data collection in this research to recognize the subconscious thoughts that are the reason behind the way sexual appeals are perceived and processed by the audience. Broad categories explain the major elements of triggers were drawn from the template analysis technique applied for data analysis. Based on the findings from the collected data, consumers associate sexual appeals with emotional connections, fun and fantasy, attractive physique and mystery. Consumers residing in the United Arab Emirates relate positively with sexual advertisements using an emotional connection or element in their advertisements. Consumers are receptive and amused by creatively crafted sexually appealing content however, the findings suggest that such advertisements receive an optimistic response only when there is some extent of meaning attached with it. Further on, the research reveals the various thematic advertisements and how they individually influence consumer purchase intention, brand recall, brand recognition and brand loyalty. The research concludes with suggestions and recommendations for theoretical and managerial purposes in relation to this subject area of study.